2016
DOI: 10.1177/0964663916647442
|View full text |Cite
|
Sign up to set email alerts
|

‘I Think it’s Rape and I Think He Would be Found Not Guilty’

Abstract: A legal definition of rape that exonerates an accused who 'reasonably believes in consent' is currently in force in a number of jurisdictions in the United Kingdom, Australia and New Zealand. Limited empirical research has investigated community and professional perceptions of the adequacy and scope of this definition of rape. The present study contributes to qualitative research on 'reasonable belief in consent' by analysing key themes from 11 focus group discussions with professionals working in the sexual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Studies have demonstrated that victims are less likely to report if they know the perpetrator or have otherwise had some form of relationship prior to the rape (Sable et al, 2006). Victims are also less likely to report if the rape was non-violent, if it happened in the victim's or the perpetrator's home (Abbey, 2011;Ceelen et al, 2019;Lovett & Horwath, 2009), if the age difference between themselves and the perpetrator is not great or if they themselves had consumed alcohol or drugs (Ceelen et al, 2019;Donde et al, 2018;Larcombe et al, 2016;Weiss & Dilks, 2016). Other social factors that may influence the propensity to report rape include the victim's faith in the police and the criminal justice system in general (Kaukinen, 2004), whether the victim thinks friends, family and others will believe them, and, more generally, how they think others might react (Donde et al, 2018;Jordan, 2001).…”
Section: Reportable Rapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that victims are less likely to report if they know the perpetrator or have otherwise had some form of relationship prior to the rape (Sable et al, 2006). Victims are also less likely to report if the rape was non-violent, if it happened in the victim's or the perpetrator's home (Abbey, 2011;Ceelen et al, 2019;Lovett & Horwath, 2009), if the age difference between themselves and the perpetrator is not great or if they themselves had consumed alcohol or drugs (Ceelen et al, 2019;Donde et al, 2018;Larcombe et al, 2016;Weiss & Dilks, 2016). Other social factors that may influence the propensity to report rape include the victim's faith in the police and the criminal justice system in general (Kaukinen, 2004), whether the victim thinks friends, family and others will believe them, and, more generally, how they think others might react (Donde et al, 2018;Jordan, 2001).…”
Section: Reportable Rapesmentioning
confidence: 99%
“…Each factor above may be related to cultural perceptions of rape and rape victims, which influence how serious victims consider the rape to be, and whether it deserves to be labelled and reported as rape (Brennan, 2016b;Larcombe et al, 2016;Stefansen & Smette, 2006). Rapes that fit the stereotype of 'real rape', where the perpetrator is a violent stranger and the rape happens in a non-familiar location, seem to be easier to report than if the perpetrator is someone known to the victim and the rape has happened in a familiar location (Bletzer & Koss, 2004;Ryan, 2011).…”
Section: Reportable Rapesmentioning
confidence: 99%
“…The above discussion reveals the confusing nature of the law, its failure to effectively communicate its own standards of consent and the gap between community and legal understandings of consent (Larcombe, Fileborn, Powell, Hanley, & Henry, 2016). In most Western criminal codes, 'reasonable belief in consent' is suggested as the benchmark for the defence to establish, and many Western jurisdictions have moved towards a communicative model of consent in order to capture the broad spectrum of behaviours or situations in which consent is not, or cannot be, freely given (Larcombe et al, 2016). This includes the consumption of alcohol and other drugs as inhibiting one's capacity to give informed consent -although this is not necessarily understood or applied in a consistent manner (Burgin, 2019).…”
Section: Dismantling Rape Culture and Rape Myths?mentioning
confidence: 99%
“…Recent rape law reforms in Victoria, Australia for example, have sought to shift the focus from the victim and the actions they took to communicate their non-consent, towards the (alleged) perpetrator and the steps they took to establish consent. However, most Western legal jurisdictions exonerate accused perpetrators who 'reasonably believe' consent was given (Larcombe et al, 2016). As I highlighted in the previous chapter, there is confusion surrounding consent in the context of rape.…”
Section: Speaking Out Onlinementioning
confidence: 99%
“…Again, sexual consent was either not taken seriously or was seen as a threatening or tiresome obligation of a sexual contract 36 . However, this also potentially dismissed how young people may feel vulnerable while negotiating consent and subject to increased coercion 36,37 . While legal consent may be framed as sexually empowering, if it is not continuous and mutual, such an emphasis can also coerce or pressure young people to give their permission for sex or to recreate dynamics of power.…”
Section: Resultsmentioning
confidence: 99%